+0  
 
0
187
3
avatar


these are my four options,

I just dont know which one it is, can you also possibly explain it?

 

Thank you

Guest May 21, 2017
Sort: 

3+0 Answers

 #1
avatar+79894 
+1

 

x^4 - 3x^3 - x^2 - 27x - 90 = 0

 

It's not easily factored, but let's guess, initially, that either 2, or -2 is one of the roots

 

Let's check - 2, first

 

(-2)^4 - 3(-2)^3 - (-2)^2 - 27(-2) - 90  =

 

16 + 24 - 4 + 54 - 90  =

 

94 - 94  =   0

 

So......-2 is a root

 

Two answers  include -2, but one of them has only 5 as the other possible root....then the possible factorization of the polynomial is either :

 

(x + 2)^2 ( x - 5)^2   but the ending constant will = 100 so this is no good

(x + 2)^3 (x - 5)       but the ending constant  = -40....no good either

(x +2) (x - 5)^3       but the ending constant is -250.....nope

 

So.......the only possible solution is  5, -2, 3i, -3i

 

Check

 

(x - 5) (x + 2) (x - 3i) (x + 3i)  =

 

( x^2 - 3x -10) ( x^2 - 9i^2) =

 

(x^2 - 3x -10) (x^2 + 9) =

 

x^4 + 9x^2 - 3x^3 - 27x - 10x^2 - 90  =

 

x^4 - 3x^3 - x^2 - 27x - 90   !!!!

 

 

 

cool cool cool

CPhill  May 21, 2017
 #2
avatar
0

Thank you

Guest May 21, 2017
 #3
avatar+1493 
+1

B; The solutions are 5, -2, 3i, and -3i

 

Let's look at the original equation:

 

\(x^4-3x^3-x^2-27x-90=0\)

 

Our goal is to get the left hand side into parts that are more manageable to work with. I'll try to explain this. We'll use the rational root theorem. This says that if a polynomial equation can be written in the form \(a_nx^n+a_{n-1}x^{n-1}+...+a_0\) and if \(a_0\) and \(a_n\) are integers, then the factor can be found by checking numbers produced by doing \(\pm\frac{dividers\hspace{1mm}of\hspace{1mm}a_0}{dividers\hspace{1mm}of\hspace{1mm}a_n}\).

 

Dividers of \(a_0:\hspace{1mm}1,2,3,5,6,9,10,15,18,30,45,90\)  

Dividers of \(a_n:\hspace{1mm}1\)

 

Therefore, check for one rational solution by doing: \( \pm\frac{1,2,3,5,6,9,10,15,18,30,45,90}{1}\)

 

-2 happens to be the first value that satisfies this equation. The opposite of that is 2, so a factor is x+2.

 

\(\frac{x^4-3x^3-x^2-27x-90}{x+2}=x^3-5x^2+9x-45\), so the monstrosity we had before goes to \((x+2)(x^3-5x+9x-45)=0\).

 

Thankfully, this is the hardest part. Now, we have to factor \((x^3-5x^2+9x-45)\) further. Find another factor by grouping:

 

\((x^3-5x^2)+(9x-45)\)

 

Factor out an x^2 from the first set of parentheses and 9 from the second set and then factor the resulting common term, which happens to be (x-5):

 

\((x^3-5x^2)+(9x-45)=x^2(x-5)+9(x-5)=(x^2+9)(x-5)\)

 

After all this effort, we have transformed \(x^4-3x^3-x^2-27x-90\) to \((x+2)(x-5)(x^2+9)\).

 

Okay, now use the zero factor principle. In other words, set each factor to zero:

 

\(x+2=0\hspace{1cm}x-5=0\hspace{1cm}x^2+9=0\) 

 

Let's focus on the easy ones first:

 

\(x=-2 \) and \(x=5\)

 

Now the harder factor:

 

\(x^2+9=0\)

\(x^2=-9\)

\(x=\pm\sqrt{-9}\)

\(x=\pm3i\)

 

Solution set is 5,2,3i, -3i

TheXSquaredFactor  May 21, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details